Awareness and misconceptions of AI among educators - Md Khambari, Mohd Najwan; Wan Bejuri, Wan Mohd Ya'akob; Zakaria, Nurul Azma; Hassan, Aslinda; Md Khambari, Mas Nida; Thamrin, Taqwan (Research and Scientific Innovation Society, 2025)
The rapid expansion of Artificial Intelligence (AI) in education has been accompanied by both opportunities and challenges, with its effective adoption being largely dependent on how well AI is understood by educators and how accurately its capabilities and limitations are perceived. Existing studies have shown that awareness levels are inconsistent and that widespread misconceptions are held across different educational levels and geographical regions, with greater familiarity being reported by higher-education lecturers compared to primary and secondary school teachers. Misconceptions such as the belief that AI will replace human teachers, assumptions that AI possesses human-like intelligence, concerns regarding the dehumanization of learning, and anxieties related to data privacy have been found to hinder meaningful AI integration in educational practice. In this study, contemporary literature on educators’ awareness and misconceptions of AI has been synthesised through a narrative review of publications published between 2020 and 2025, and patterns of awareness, dominant misconceptions, and factors influencing AI adoption have been analysed. Findings indicate that awareness remains highly variable, misconceptions persist across contexts, and institutional support, digital literacy, and access to professional development are significant determinants of educators’ readiness to use AI. Based on these insights, it is suggested that targeted AI literacy initiatives, structured professional development, and clear institutional policies are urgently required to dispel misconceptions and promote ethical, confident, and responsible use of AI in education. This review is expected to contribute to ongoing scholarly and policy discussions by providing evidence-based guidance for policymakers, institutions, and training providers to strengthen educators’ preparedness for AI-enhanced teaching and learning.